2018
DOI: 10.3390/app8112056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interfacial Intermetallic Growth on the Mechanical Properties of Sn-37Pb Solder Joints under Extreme Temperature Thermal Shock

Abstract: Solder joints in thermally uncontrolled microelectronic assemblies have to be exposed to extreme temperature environments during deep space exploration. In this study, extreme temperature thermal shock test from −196 °C to 150 °C was performed on quad flat package (QFP) assembled with Sn-37Pb solder joints to investigate the evolution and growth behavior of interfacial intermetallic compounds (IMCs) and their effect on the pull strength and fracture behavior of Sn-37Pb solder joints under extreme temperature e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Lapisan Cu6Sn5 membentuk lapisan seperti kerang. Menurut [9], difusi atom Cu berguna untuk pertumbuhan IMC yang lebih cepat dan akan membentuk lapisan seperti kerang seiring dengan meningkatnya temperatur yang teridentifikasi sebagai fasa Cu6Sn5. Terdapat pula lapisan Cu3Sn yang terbentuk secara planar dan berdekatan dengan substrat Cu.…”
Section: Hasil Pengujian Scanning Electronunclassified
“…Lapisan Cu6Sn5 membentuk lapisan seperti kerang. Menurut [9], difusi atom Cu berguna untuk pertumbuhan IMC yang lebih cepat dan akan membentuk lapisan seperti kerang seiring dengan meningkatnya temperatur yang teridentifikasi sebagai fasa Cu6Sn5. Terdapat pula lapisan Cu3Sn yang terbentuk secara planar dan berdekatan dengan substrat Cu.…”
Section: Hasil Pengujian Scanning Electronunclassified
“…Realized or not, it is also one of the key elements in traditional macro-welding technologies. Recently, this is being widely used in micro-and nanoscales to develop new joining processes, ranging from nanodevices [28] to electronic packaging [29,30], soldering [31] to light alloy (Ti, Al) [32,33], and high-strength steel joining [34]. The goal of design strategy is to meet the performance requirements of as-fabricated joints through the proper determination of the necessary number of IMCs, layered structures, phases, intrinsic properties of used materials (e.g., hardness, grain size, etc.…”
Section: Micro/nanoscale Joined Interfacesmentioning
confidence: 99%
“…Fushimi et al [29] reported that hard copper materials and fine grains could suppress the crack propagation from the thermal fatigue of ultrasonically bonded copper joints for electronic devices by providing more grain boundaries at the interface, which can be controlled by longer friction time and grain refinement. When Hang et al [31] studied the interfacial intermetallic growth of Sn-37Pb solder joints, under −196 • C to 150 • C thermal shocking, they found that plane-type IMCs and layered Cu 3 Sn could grow at the interface because of the bulk diffusion and grain-boundary diffusion, resulting in the ductile fracture to mixed ductile-brittle fracture transition and the reduction of joint strength. It is speculated that brittle fracture could also be further improved by designing the shape of formed interfacial IMCs and controlling the diffusion.…”
Section: Micro/nanoscale Joined Interfacesmentioning
confidence: 99%